The impact of keeping a religious beard in the COVID-19 pandemic: an online cross-sectional survey study exploring experiences of male medical healthcare professionals - Hamed, Amer; Latif, Asam; Haris, Mohammad; Patel, Sufyan; Patel, Muhammad I; Rahman Mustafa, Syed Abdur; Khan, Omeair; Shoaib, Ahmad; Waqar, Salman (International Journal of Human and Health Sciences (IJHHS), 2022)
In the UK, there has been a disproportionate impact of Coronavirus disease (COVID-19) on individuals from Black Asian & Minority Ethnic (BAME) groups including those working in the NHS. Many male NHS staff have been asked to remove their beards for the ‘fit test’. However this can have negative implications on their spiritual, psychological & emotional wellbeing. . This paper surveyed the responses of 469 healthcare BAME healthcare professionals (HCPs) with beards regarding the challenges they face in regard to personal protective equipment (PPE), mask fit testing and attitude of employers and colleagues. Professional discrimination through fit testing rejection, unavailability or inadequate PPE and the pressure to shave beards were reported to be unpleasant and underreported outcomes of the pandemic. NHS trusts and hospitals need to adjust their policies to ensure inclusivity in their COVID-19 arrangements. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 113-122